2016
DOI: 10.3390/molecules21030264
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Health

Abstract: Nowadays, there are some molecules that have shown over the years a high capacity to act against relevant pathologies such as cardiovascular disease, neurodegenerative disorders or cancer. This article provides a brief review about the origin, bioavailability and new research on curcumin and synthetized derivatives. It examines the beneficial effects on health, delving into aspects such as cancer, cardiovascular effects, metabolic syndrome, antioxidant capacity, anti-inflammatory properties, and neurological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
261
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(293 citation statements)
references
References 200 publications
(221 reference statements)
1
261
0
5
Order By: Relevance
“…Nonetheless, although inexpensive, apparently well tolerated, and potentially active, curcumin has yet not been approved for treatment of any human disease/ailment [20]. Despite thousands of research papers, wide range of pharmacological activities of curcumin reported in the past decades, more than 120 reported clinical trials, still a paradox and uncertainty remains regarding the pharmacology of curcumin owing to its physicochemical properties leading to the poor systemic bioavailability [23,24].…”
Section: Curcumin Research: What Is the Current Scenario?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, although inexpensive, apparently well tolerated, and potentially active, curcumin has yet not been approved for treatment of any human disease/ailment [20]. Despite thousands of research papers, wide range of pharmacological activities of curcumin reported in the past decades, more than 120 reported clinical trials, still a paradox and uncertainty remains regarding the pharmacology of curcumin owing to its physicochemical properties leading to the poor systemic bioavailability [23,24].…”
Section: Curcumin Research: What Is the Current Scenario?mentioning
confidence: 99%
“…Just like another well studied biomolecule, quercetin [5][6][7]13,14], curcumin has also received considerable attention over the past decades, which is mainly due to its diverse biological activities, including but not limited to antioxidant, anti-inflammatory, anti-arthritic, anti-ulcer, anti-diabetic, anti-bacterial activities and its potential therapeutic applications in a large number of diseases including but not limited to cancer and neurodegenerative diseases (Figure 1) [4,11,12,[15][16][17][18][19]. Hence, curcumin is used as a supplement/neutraceutical in several countries, including but not limited to India, Japan, America, Thailand, China, Korea, Turkey, South Africa, Nepal, Bangladesh, Sri Lanka and Pakistan owing to its perceived potential health benefits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is the compound responsible for the chemical and biological properties of this spice, as well as its color and taste. Numerous studies have shown that curcumin is associated with antioxidant, anti-inflammatory, antimutagenic, antimicrobial, and anticancer effects, mitigating chronic diseases and increasing longevity [37,38]. HSPs, HSF1, and histone deacetylase (HDAC) 6 are upregulated in cancer.…”
Section: Curcuminmentioning
confidence: 99%
“…What is more, extensive research over the last half century has revealed several important functions of curcumin. Such effects include antioxidant, anti-inflammatory, antimicrobial, hepatoprotective, anticarcinogenic, thrombosuppressive and cardiovascular [2].…”
Section: Mini Reviewmentioning
confidence: 99%